1999
DOI: 10.1190/1.1444688
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency reflections in granite? Delineation of the weathering front in granodiorite at Piñon Flat, California

Abstract: We analyze data from two orthogonal seismic lines 336 m in length collected at Piñon Flat, California, over weathered granodiorite bedrock. Each line was made up of 10 reversed segments 84 m in length. We analyzed the first arrivals from these data and found dramatic variations in velocity along the profiles. An upper layer (approximately 2-m thick) known from trenching to be composed of soil and sandy grus had measured velocities ranging from 400 to 700 m/s. Velocities inferred from refraction analysis of fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…This is illustrated by experiments carried out at depth through boreholes or galleries far from any weathering (Jamtlid et al, 1984;€ Hayles et al, 1999;Jeanne et al, 2012). Other field studies demonstrated the sensitivity of seismic methods to alteration fronts (Lee and de Freitas, 1990;Radzevicius and Pavlis, 1999). Therefore, combining seismic and electric methods is appropriate to characterise weathering of fractured crystalline rocks.…”
Section: Geophysical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is illustrated by experiments carried out at depth through boreholes or galleries far from any weathering (Jamtlid et al, 1984;€ Hayles et al, 1999;Jeanne et al, 2012). Other field studies demonstrated the sensitivity of seismic methods to alteration fronts (Lee and de Freitas, 1990;Radzevicius and Pavlis, 1999). Therefore, combining seismic and electric methods is appropriate to characterise weathering of fractured crystalline rocks.…”
Section: Geophysical Methodsmentioning
confidence: 99%
“…Acworth,1987;Neuman, 2005;Roques et al, 2014). For example, the depth of present day and paleo-weathering fronts have been estimated as a few metres (Virgili et al, 1974), several tens of metres (Radzevicius and Pavlis, 1999;Dewandel et al, 2006), hectometres (Genter and Traineau, 1996;Olesen et al, 2007), or up to a kilometre (Luthi, 2005). The factors governing deepening, and therefore lateral and depth extents of weathering in the vicinity of major structures, still require investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al 1994;Radzevicius and Pavlis 1999;Juhlin et al 2002;Juhlin and Stephens 2006;Eaton 2003;Schmelzbach et al 2007;Malehmir et al 2012a;Heinonen et al 2013;Ehsan et al 2014). The mining sector is one of the fields where the seismic reflection method has shown great utility to complement the more generally applied gravimetric, magnetic, electrical and electromagnetic methods.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, due to the advances in electronics such as 24 bit A/D converters and processing techniques, the seismic reflection method has gained a dramatic increase in the number of applications to hard-rock exploration (e.g. Kim et al 1994;Radzevicius and Pavlis 1999;Eaton 2003). The mining industry is one of the fields where the seismic reflection method has shown great utility to complement the more generally applied gravimetric, magnetic, electrical and electromagnetic methods in VSC.…”
Section: Methodsmentioning
confidence: 99%